Determination of factors associated with natural soil suppressivity to potato common scab - Sagova-Mareckova, Marketa; Daniel, Ondrej; Omelka, Marek; Kristufek, Vaclav; Divis, Jiri; Kopecky, Jan (PloS one, 2015)
Common scab of potatoes is a disease, which is difficult to manage due to complex interactions of the pathogenic bacteria (Streptomyces spp.) with soil, microbial community and potato plants. In Bohemian-Moravian Highlands in the Czech Republic two sites (Vyklantice and Zdirec) were selected for a study of common scab disease suppressivity. At both sites, a field with low disease severity occurs next to one with high severity and the situation was regularly observed over four decades although all four fields undergo a crop rotation. In the four fields, quantities of bacteria, actinobacteria and the gene txtB from the biosynthetic gene cluster of thaxtomin, the main pathogenicity factor of common scab, were analyzed by real-time PCR. Microbial community structure was compared by terminal fragment length polymorphism analysis. Soil and potato periderm were characterized by contents of carbon, nitrogen, phosphorus, sulphur, calcium, magnesium, and iron. Quality of organic matter was assessed by high performance liquid chromatography of soil extracts. The study demonstrated that the suppressive character of the fields is locally specific. At Zdirec, the suppressivity was associated with low txtB gene copies in bulk soil, while at Vyklantice site it was associated with low txtB gene copies in the tuberosphere. The differences were discussed with respect to the effect of abiotic conditions at Zdirec and interaction between potato plant and soil microbial community at Vyklantice. Soil pH, Ca soil content or cation concentrations, although different were not in the range to predict the disease severity. Low severity of common scab was associated with low content of soil C, N, C/N, Ca and Fe suggesting that oligotrophic conditions may be favorable to common scab suppression.
Keywords: multigenová rodina; Plant Diseases; polymorfismus délky restrikčních fragmentů; Multigene Family; indoly; Genes, Bacterial; Soil Microbiology; Indoles; piperaziny; půdní mikrobiologie; Streptomyces; Polymorphism, Restriction Fragment Length; bakteriální geny; Plant Tubers; Solanum tuberosum; Piperazines; hlízy rostlin; nemoci rostlin